IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA HINDU BERBASIS KEARIFAN LOKAL DI SMA NEGERI SE-KOTA PALANGKA RAYA - pranata, Pranata; Natalia, Krisma; Sarwinda, Sarwinda (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2026)
Hindu Religious Education in Central Kalimantan demonstrates distinctive characteristics due to its close interaction with the beliefs and ritual practices of Kaharingan Hinduism, which remain actively practiced within local communities. Despite this cultural richness, the implementation of Hindu Religious Education incorporating Kaharingan local content at the senior high school level remains limited, particularly in terms of the availability of structured teaching materials and systematic instructional design. This study aims to examine the implementation of Hindu Religious Education based on Kaharingan Hinduism local content in public senior high schools in Palangka Raya City. This study employed a descriptive qualitative research design. Data were collected through classroom observations, in-depth interviews, and document analysis. Informants were selected using purposive sampling and included school principals, Hindu Religious Education teachers, and students. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings reveal that the integration of Kaharingan Hinduism local content has been implemented through curriculum alignment and teachers’ pedagogical initiatives, particularly by integrating local values, rituals, and religious teachings into classroom instruction. However, the implementation largely depends on individual teachers’ competencies and initiatives due to the absence of standardized teaching materials that systematically present Kaharingan Hindu teachings. Therefore, the development of context-based instructional materials and the enhancement of teachers’ professional competencies are essential to support effective, meaningful, and sustainable Hindu Religious Education.